Effects of typhoon Roke and Haitang on phytoplankton community structure in northeastern South China sea - Yingjie Mao (Taylor & Francis Group, 2019)
The influence of typhoon and Kuroshio intrusion process on the natural phytoplankton assemblages in the northeastern South China Sea (neSCS) was examined during a cruise in summer 2017. One hundred ninety-six seawater samples were collected and analyzed in the neSCS. In total, 299 species were identified belonging to 82 genera, mostly dominated by Bacillariophyta (159), followed by Dinophyta (132), Cyanophyta (4) and Chrysophyta (4). Among all, Thalassionema nitzschioides, Thalassionema frauenfeldii, Thalassiosira minima, in Bacillariophyta, Prorocentrum lenticulatum, Prorocentrum compressum in Dinophyta, and Trichodesmium thiebautii, in the Cyanophyta were the most dominated species, respectively. Correlation analysis shows compared with other groups Bacillariophyta was mostly influenced by silicate, whereas, Dinophyta and Cyanophyta showed significant correlation with temperature, salinity, phosphate, and nitrate. After the typhoon, the higher abundance of Dinophyta was observed, whereas it was lower in case of Bacillariophyta and Cyanophyta, shows typhoon “Roke“ and ”Haitang” had a significant influence on the phytoplankton assemblages, which could be manifested by the variations of total phytoplankton abundance in the surface water of neSCS. Overall, our present study provides the latest in-depth information about how the environmental factors influencing the phytoplankton density and diversity in the neSCS during summer.